E-learning platform: Data protection in the educational scope - Cabrera Delgado, José Manuel (Avances en Supervisión Educativa, 2020)
The suspension of face-to-face teaching activity, derived from the health crisis caused by COVID-19, had as a direct consequence that the different educational Administrations turned their eyes towards distance learning. Mainly, due to the possibility of making the prevention of the disease compatible with maintaining an interpersonal relationship with the students as closely as possible. In this context, the use of different educational platforms has become essential and with it the need to work with personal data of all those involved in the process, making the security and protection of data a concern of institutions and governments that should be managed from all ambits involved.The purpose of this article is to make visible some of the most complex and relevant aspects in the treatment of personal data by online learning platforms, as well as to determine those actions by the Administration or educational centers that must be followed for better protection of users, in accordance with the rights and obligations imposed by current regulations. For this, and as an example, two of the platforms most widely used by Spanish teachers and students are analyzed: G Suite for Education and Microsoft 365 Education.
Keywords: educational platform; e-learning; Data Protection; Privacy; G Suite for Education; Microsoft 365 Education